Analisis Potensi Ekspor Produk Ikan Asin Jambal Roti di Kabupaten Pangandaran - Bambang mutaqin; Sari Usih Natari (FEB-UP Press, 2021)
Pangandaran is the most potential tourism area in West Java. The local government also has plans to develop the Pangandaran area into a world-class tourist destination. An alternative approach taken in developing the Pangandaran area is the concept of community entrepreneurship-based development. This is focused on the catch of fishermen that have high value, one of which is jambal fish. Jambal fish itself can be processed by curing, some are vegetables with yellow coconut milk, pindang gombrang, and some are made of salted fish. There is so much production of salted jambal roti fish that many cannot sell well. A marketing strategy is needed by exporting jambal roti salted fish to several Asian countries. The purpose of this research is to identify the extent of export activities carried out on some of the salted fish jambal roti businessmen in Pangandaran Regency and what is the impact on the welfare of local residents. The result of this research is the export potential of salted jambal roti fish which has become a culinary icon that can be applied in the Pangandaran Regency area.